2001
DOI: 10.1039/b004881j
|View full text |Cite
|
Sign up to set email alerts
|

Autothermal methanol reforming for hydrogen production in fuel cell applications

Abstract: Fuel cell powered electric cars using on-board methanol reforming to produce a hydrogen-rich gas represent a low-emissions alternative to gasoline internal combustion engines (ICE). In order to exceed the well-to-wheel efficiencies of 17% for the gasoline ICE, high-efficiency fuel cells and methanol reformers must be developed. Catalytic autothermal reforming of methanol o †ers advantages over endothermic steam-reforming and exothermic partial oxidation. Microreactor testing of copper-containing catalysts was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 11 publications
1
96
0
1
Order By: Relevance
“…The first reaction mechanism proposed as sequence the formation of H 2 and CO primarily from MD, and then the water-gas shift (WGS) would occur to produce CO 2 and H 2 [28]. Other authors stated later that the correct pathway involves the formation of CO 2 and H 2 through direct MSR, followed by the RWGS reaction [29]. According to the first mechanism, the amount of CO should be equal or higher to the equilibrium of the RWGS reaction and this condition must be verified for the whole temperature range [11,15].…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…The first reaction mechanism proposed as sequence the formation of H 2 and CO primarily from MD, and then the water-gas shift (WGS) would occur to produce CO 2 and H 2 [28]. Other authors stated later that the correct pathway involves the formation of CO 2 and H 2 through direct MSR, followed by the RWGS reaction [29]. According to the first mechanism, the amount of CO should be equal or higher to the equilibrium of the RWGS reaction and this condition must be verified for the whole temperature range [11,15].…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…Recent papers have discussed the POM reaction [22][23][24], as well as the combined process for production of H 2 [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The Cu/ZnO/Al 2 O 3 catalyst, which is traditionally used for low-temperature gas-shift and methanol synthesis, has been widely used in these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This efficiency is to be compared with that of a PEM fuel cell operated with hydrogen from an autothermal methanol reformer. Geissler et al found that only 4% of the methanol's energy content is lost during the reforming and gas clean-up process (preferential CO oxidation) [23]. Only about 50% of the hydrogen energy is converted to electrical energy, and about 20% of the generated electric power is used for driving auxiliary equipment (compressors, pumps).…”
Section: Resultsmentioning
confidence: 99%